Glutamine depletion in patients with Crimean‐Congo hemorrhagic fever. Issue 12 (13th August 2020) - Aydin, Hüseyin; Engin, Aynur; Keleş, Sami; Ertemur, Zeynep; Hekim, Nezih
Abstract: Crimean‐Congo hemorrhagic fever (CCHF) is a viral disease. There is not enough knowledge about plasma amino acid levels in CCHF. Therefore, we investigated plasma amino acid levels in patients with CCHF and the association between the levels of these amino acids and disease severity. The plasma amino acid levels (including glutamate [Glu], aspartate [Asp], glutamine [Gln], asparagine [Asn] and gamma‐aminobutyric acid [GABA]) in CCHF patients and controls were measured by using liquid chromatography‐mass spectrometry. Plasma levels of Gln were lower while Asp, Glu, and GABA levels were higher in patients. In fatal CCHF patients, we found the plasma level of Asn was increased whereas the plasma level of GABA was decreased. This study is the first in the literature to evaluate the plasma Gln, Glu, Asn, Asp, and GABA levels in CCHF patients. We found that the plasma Gln levels were significantly lower in CCHF patients while Asp, Glu, and GABA levels were elevated. Considering that these amino acids are important for immune cells, the plasma amino acid levels of CCHF patients may contribute to the understanding of the pathophysiology of disease and it can be important for supportive treatment of CCHF. Highlights: This study highlight is to emphasize that prognosis can be improved by replacing decreased plasma glutamine levels in CCHF patients whose plasma glutamine levels were decreased during the infection period.